Farmers’ social networks and adoption of modern crop varieties in India - Negi, Digvijay S.; Kumar, Anjani; Tripathi, Gaurav; Birthal, Pratap Singh (International Food Policy Research Institute, 2020)
Using information on varietal adoption of important cereal crops from a large-scale survey in India, this paper investigates “how social networks influence technology adoption behaviour of farm households.” Our key innovation is that unlike many other studies that consider village-level adoption rates as a proxy for social networks, we identify a farm household's peer group based on caste and sources of information within a region. In the context of rural India, such networks are more relevant because of the historical evolution of the caste system based on similarities in the socio-cultural and occupational characteristics of households that provide greater stability and cohesiveness to the networks. Our findings show that the social networks of modern crop varieties’ adopters are stronger than those of their non-adopters. Further, it is found that the adoption of modern varieties is strongly influenced by social networks, but their influence varies across crops depending on the stage of varietal diffusion.